Wetland Ecology : Principles and Conservation / [electronic resource] - Keddy, Paul A. (Cambridge : Cambridge University Press, 2010)
Richly illustrated and packed with numerous examples, this unique global perspective introduces wetland ecology from basic principles to advanced applications. Thoroughly revised and reorganised, this new edition of this prize-winning textbook begins with underlying causal factors, before moving on to more advanced concepts that add depth and context. Each chapter begins with an explanation of the basic principles covered, illustrated with clear examples. More difficult concepts and exceptions are introduced only once the general principle is well-established. Key principles are now discussed at the beginning of the book, and in order of relative importance, enabling students to understand the most important material without wading through complex theory. New chapters on wetland restoration and wetland services draw upon practical examples from around the world, providing a global context, and a new chapter on research will be particularly relevant to the advanced student planning their own studies.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Wetland ecology; Wetland conservation